Identification of dynamical characteristics for distributed parameters systems from measured vibration data - Khiem, Nguyen Tien; Mai, Dao Nhu; Dac, Nguyen Van; Khoa, Nguyen Viet (Vietnam Journal of Mechanics, 1995)
This article is devoted to determinate the dynamical characteristics (Natural Frequencies, Mode Shapes, Damping Ratio) of elastic beam from measured responce auto-spectrum. Developed here method is based on the assumptions of smallness of the damping and sparse distribution of natural frequencies. Accuracy and practical meaning of the method are confirmed by the agreement of the theory with experiments.